Pectinase production by Aspergillus niger isolated from decomposed apple skin (Bangladesh Journal of Scientific and Industrial Research, 2013)
Pectinase activity among twelve different fungal strains, Aspergillus niger IM09 was identified as a potential one to produce maximal level 831 U/g at pH 4.0. Media composition, incubation temperature, incubation time, substrate concentration, aeration, inoculum size, assay temperature and nitrogen sources were found to effect pectinase activity. Moisture content did not affect the activity significantly. Media composition was varied to optimize the enzyme production in solid state fermentation. It was observed that the highest pectinase activity of 831.0 U/g was found to produce in presence of yeast extract as a nitrogen source in combination with ammonium sulfate in assay media. Aeration showed positive significant effects on pectinase production 755 U/g at 1000 ml flasks. The highest pectinase production was found at 2 g pectin (521 U/g) used as a substrate. Pectinolytic activity was found to have undergone catabolite repression with higher pectin concentration (205 U/g at 5 g pectin). The incubation period to achieve maximum pectinase activity by the isolated strain Aspergillus niger IM09 was 3 days, which is suitable from the commercial point of view. DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15410 Bangladesh J. Sci. Ind. Res. 48(1), 25-32, 2013